2015
DOI: 10.1177/1098300715588282
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of a Self-Management Intervention to Increase On-Task Behavior With Individuals Diagnosed With Attention-Deficit/Hyperactivity Disorder

Abstract: Attention-deficit/hyperactivity disorder (ADHD) is one of the most prevalent disorders in school-age children. Children with ADHD often have difficulty at school and at home. Medication is a common treatment for children with ADHD; however, it has been shown to be more effective when combined with behavioral interventions. Self-management has extensive research support showing its effectiveness for children with ADHD primarily in academic settings. The purpose of this study was to examine the impact a self-man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 27 publications
(38 reference statements)
0
9
0
6
Order By: Relevance
“…As one example, Barton et al (2018) used a combination of peer modeling, systematic prompting, and contingent (i.e., dependent upon performing the targeted behavior) reinforcement to teach board game play and social behaviors to four young children with diverse disabilities (i.e., autism, visual impairments, cognitive and communication delays). In another example, Slattery, Crosland, and Iovannone (2016) employed a self-management plan paired with reinforcement to teach children with attention deficit/hyperactivity disorder to increase on-task behaviors in home settings. Applied behavior analysis strategies can also be used to teach educators and other professionals to correctly implement specific skills (e.g., behavior support plans; Pinkelman & Horner, 2017).…”
Section: Myth: Relevant Only For Those With Problem/challenging Behavmentioning
confidence: 99%
“…As one example, Barton et al (2018) used a combination of peer modeling, systematic prompting, and contingent (i.e., dependent upon performing the targeted behavior) reinforcement to teach board game play and social behaviors to four young children with diverse disabilities (i.e., autism, visual impairments, cognitive and communication delays). In another example, Slattery, Crosland, and Iovannone (2016) employed a self-management plan paired with reinforcement to teach children with attention deficit/hyperactivity disorder to increase on-task behaviors in home settings. Applied behavior analysis strategies can also be used to teach educators and other professionals to correctly implement specific skills (e.g., behavior support plans; Pinkelman & Horner, 2017).…”
Section: Myth: Relevant Only For Those With Problem/challenging Behavmentioning
confidence: 99%
“…Used in combination with SOC-IS, it has proven very useful in studies analyzing children's behavior in the classroom (Anguera, Espinosa, & Santoyo, 2002;Anguera, Santoyo, & Espinosa, 2003;Espinosa, Anguera, & Santoyo, 2004) and in other observational studies (Hernández-Mendo & Anguera, 1998;Anguera & Losada, 1999;Aragón, Lapresa, Arana, Anguera & Garzón, 2017;Castañer et al, 2016;Gorospe & Anguera, 2000;Herrero, 2000;López, Valero, Anguera & Díaz, 2016;Morillo, Reigal & Hernández-Mendo, 2015;Perea, Castellano, Alday & Hernández-Mendo, 2012). We believe that polar coordinate analysis would also be a valuable tool for analyzing the impact of self-regulation interventions in children with high rates of behavior transitions (Norris, 2016;Slattery, et al, 2016). Following Cochran's proposal (1954), the prospective adjusted residuals (positive lags) and retrospective adjusted residuals (negative lags) generated in the lag sequential analysis were used, respectively, to compute prospective and retrospective Z sum values, which in turn were used to calculate vector length and angle.…”
Section: Polar Coordinate Analysismentioning
confidence: 99%
“…The effects of reinforcement strategies on academic activity have also been analyzed (Martens, 1990;Martens, Halperin, Rummel, & Kilpatrick, 1990;Santoyo et al, 2000). Forms and means of teacher-student interactions can be described by the matching law (Torres, 2012;Delgado, 2013), and two very recent studies have shown that reinforcement interventions focused on self-regulation can improve on-task behavior (Norris, 2016;Slattery, Crosland, & Iovannone, 2016). However, it is also necessary to collect information on classroom events that occur that influence the development of diverse behavioral patterns, and in particular the behavior stream of individual students and their social interaction with peers.…”
Section: Introductionmentioning
confidence: 99%
“…Melihat keterkaitan antara masalah inatensi dengan kesulitan yang dapat dialami anak dalam memenuhi tuntutan di sekolah, perlu adanya intervensi yang diberikan pada AR untuk meningkatkan kemampuannya mempertahankan atensi dalam mengerjakan suatu tugas tanpa melakukan kegiatan lain di luar tugas atau disebut dengan perilaku on-task. Untuk menyiapkan anak agar mampu bekerja secara mandiri dan dapat menampilkan perilaku on-task, orang dewasa tidak dapat hanya menunggu atau mengharapkan anak untuk melakukan dengan sendirinya, melainkan diperlukan intervensi untuk meningkatkan perilaku tersebut, khususnya pada anak dengan masalah atensi (Slattery, 2013).…”
unclassified
“…Perilaku off-task verbal diartikan sebagai verbalisasi yang tidak berkaitan dengan tugas yang sedang dikerjakan (misalnya berbicara dengan orang lain mengenai hal yang tidak berkaitan dengan tugas, berteriak, atau menangis). Kemudian, perilaku off-task pasif diartikan sebagai tidak terlibatnya anak terhadap suatu tugas atau rutinitas yang sedang dikerjakan dalam jangka waktu minimal 5 detik yang ditunjukkan dengan perilaku pasif (misalnya melamun, tidak melihat ke arah tugas) (Slattery, 2013).…”
unclassified